Key Factors Influencing Madiun Entrepreneurs in Starting Culinary Businesses: An Exploratory Factor Analysis Approach - Utomo, Prasetyo Yekti; Setyawan, Dimas Ari; Thousani, Hifzhan Frima (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to identify the factors influencing entrepreneurs' decisions to enter the culinary business sector in Madiun, Indonesia. Using a quantitative approach with Exploratory Factor Analysis (EFA), the study examines both internal and external factors that shape decision-making processes. Data were collected from 100 respondents through a structured questionnaire and analyzed using SPSS software. The results indicate that three main factors influence entrepreneurs: Product, Motivation, and Socio-Cultural factors. The Product factor, which includes variables such as ease of operation, market demand, and profitability, was found to be the most significant. Motivation, which encompasses personal skills, entrepreneurial interest, and self-empowerment, plays a key role in driving business choices. The Socio-Cultural factor reflects the influence of the environment, educational background, and available resources. These findings provide valuable insights for current and aspiring entrepreneurs, as well as policymakers, by highlighting the key drivers of success in the culinary business. The study suggests that the accessibility and growth potential of the culinary sector in Madiun make it an attractive industry for entrepreneurs seeking both personal and financial fulfillment